2004
DOI: 10.1088/1126-6708/2004/10/017
|View full text |Cite
|
Sign up to set email alerts
|

Tachyonic preheating using 2PI-1/N dynamics and the classical approximation

Abstract: We study the process of tachyonic preheating using approximative quantum equations of motion derived from the 2PI effective action. The O(N ) scalar (Higgs) field is assumed to experience a fast quench which is represented by an instantaneous flip of the sign of the mass parameter. The equations of motion are solved numerically on the lattice, and the Hartree and 1/N-NLO approximations are compared to the classical approximation. Classical dynamics is expected to be valid, since the occupation numbers can rise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 64 publications
(141 reference statements)
2
125
0
Order By: Relevance
“…The classical approximation for a tachyonic transition has been compared with quantum methods like the 2PI-method in [29], and it turned out that the two approximations agreed for the times and couplings used here, giving further support for both.…”
Section: Tachyonic Transitionmentioning
confidence: 55%
“…The classical approximation for a tachyonic transition has been compared with quantum methods like the 2PI-method in [29], and it turned out that the two approximations agreed for the times and couplings used here, giving further support for both.…”
Section: Tachyonic Transitionmentioning
confidence: 55%
“…Stated differently, this concerns the large field or large occupancy limit, which is relevant for important phenomena such as nonequilibrium instabilities or wave turbulence encountered in our study. The classicality condition has been verified in detail by comparing quantum to classical-statistical results in the context of scalar quantum field dynamics [2,32,33,39] and coupled to fermions [41,42].…”
Section: Scalar Model and Initial Conditionsmentioning
confidence: 93%
“…The important advantage for scalars is that powerful resummation techniques exist for the description of the entire evolution in quantum field theory. It has been demonstrated that classical-statistical descriptions have a well understood range of validity for which they accurately describe the dynamics of the underlying quantum theory [2,[32][33][34].…”
Section: Jhep05(2014)054mentioning
confidence: 99%
“…Refs. [17,19,20,21]). We consider both a trilinear coupling χσ 2 a and a quartic coupling χ 2 σ 2 a .…”
Section: φ(T) + [3h(t) + υ φ (T)]φ(t) + V ′ [φ(T)] = 0 (12)mentioning
confidence: 99%